6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y
9y - 4x
It is equivalent to 3(4x+3y) when factored
4y + 3w + 4x + 9y + 7x - 7w (combine like terms)-4w + 11x + 13y
12y+3=9y-15 3y=-18 y=-6
6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y
p + q + r = (2x - 9y) + (5y + 6 - 4x) + (3x + 3y - 5) = x - y + 1
9y - 4x
It is equivalent to 3(4x+3y) when factored
x^2(2x - 3y)(4x^2 + 6xy + 9y^2)
35
second equation x 2: 4x + 6y = 4 subtract first equation: 9y = 3 so y = 1/3 and x = 1/2
There are two simultaneous equations, so to solve for y, eliminate x: 1) 2x + 3y = 3 2) 4x - 3y = 9 Multiply equation (1) by 2 giving: 1) 4x + 6y = 6 2) 4x - 3y = 9 Next, subtract equation (2) from equation (1), giving: (4x - 4x) + (6y - -3y) = 6 - 9 → 9y = -3 → y = -1/3
5x + 6y + 3y - 2x you have to add like terms. add the y terms and then the x terms 9y + 3x this is your answer
It is an algebraic expression that can be simplified to: 5x+9y+5
2x - 3y = 5 => 3y = 2x - 5 has a gradient of 2/3 9y + bx = 4 => 9y = -bx + 4 has a gradient of -b/9 The two gradiends must be the same if the two lines are parallel: 2/3 = -b/9 so that b = -6
Let's see if I can answer this. 4X + 6Y + 3Y + 4W + 6X - 7W = (4 + 6)X + (6 + 3)Y + (4 - 7)W = 10X + 9Y - 3W